The Effectiveness of Motivation Through Posse Strategy On Improving The EFL Learners’ Reading Comprehension Skills - Andrian, Diyah Iis (Jurnal Ilmiah Humanika, 2018)
Reading motivation is seen as the most vital element that affects reading comprehension skills. It is also viewed as one of the main factors for foreign language students that assists them to read more effectively. Researchers have found that teaching reading strategies is the key in developing the students‘ comprehension. The POSSE is one of the interesting strategies used in reading. It refers to the activity in which POSSE activates their prior knowledge about the topic and connect it with the information contained in the text (Englert & Marriage in Westwood, 2008: 45). This action research paper aims to investigate the effect of motivation through POSSE strategy on comprehending English texts. It concentrates on reading comprehension mainly because reading is one of the four basic skills in English as a foreign language (EFL). This study used a descriptive analytical approach to examine how motivation through POSSE strategy affects the students‘ reading comprehension skills among the second semester students of English department faculty of letters at Universitas Pamulang (UNPAM). The data were collected by means of questionnaires and tests from 60 participants, and they were analyzed by using t-test to find out the effect of motivation through POSSE strategy on the students‘ reading comprehension. This study leads to the findings that: POSSE is one of the motivational techniques which improves the EFL intrinsic motivation to read, motivation affects on EFL learners‘ reading comprehension skills, and different techniques of teaching reading comprehension are helpful in comprehending English texts. Further, the study revealed that the motivation gave significant effect on the students‘ reading comprehension skills. Finally, the writer recommends that the different reading strategies should be taught to EFL students to improve the students‘ motivation to read and understand the reading texts.